Oxytocin and positive couple interaction affect the perception of wound pain in everyday life - Pfeifer, Ann-Christin; Schröder-Pfeifer, Paul; Schneider, Ekaterina; Schick, Maren; Heinrichs, Markus; Bodenmann, Guy; Ehlert, Ulrike; Herpertz, Sabine; Läuchli, Severin; Eckstein, Monika; Ditzen, Beate (Molecular pain, 2020)
A large body of animal and human laboratory research has linked social interaction and support to pain perception, with a possible role for the neuropeptide oxytocin as a neuroendocrine mediator. However so far, it has been unclear whether these effects translate to ecologically valid everyday life behavior and pain perception. In a randomized placebo-controlled study, a standard suction blister skin wound was induced to N = 80 romantic couples (N = 160 individuals). Couples then received intranasal oxytocin or placebo twice daily and were either instructed to perform a positive social interaction (partner appraisal task, PAT) once in the laboratory and two times during the following five days, or not. During these days, all participants reported their subjective pain levels multiple times a day using ecologically momentary assessment. Results from hierarchical linear modeling suggest that pain levels within the couples were inter-related. In men, but not in women, oxytocin reduced pain levels. Women reported lower pain levels in the group of positive social interaction, while this effect did not show in men. These results suggest that intranasal oxytocin might have sex-specific effects with pain reducing effects in men but the opposite effects in women. In contrast, especially women benefit from positive interaction in terms of dampened pain levels after positive interaction. The results add to the evidence for health-beneficial effects of positive couple interaction and point to underlying neuroendocrine mechanisms in everyday life pain specifically. The sex-specific effects, in particular, may have implications for psychopharmacological treatment of pain in men and women.
Gesehen am 10.06.2020